Efficiency of Thermally Activated Delayed Fluorescence Sensitized Triplet Upconversion Doubled in Three‐Component System. Issue 5 (14th December 2021) - Yurash, Brett; Dixon, Alana; Espinoza, Carolina; Mikhailovsky, Alexander; Chae, Sangmin; Nakanotani, Hajime; Adachi, Chihaya; Nguyen, Thuc‐Quyen
Abstract: As in many fields, the most exciting endeavors in photon upconversion research focus on increasing the efficiency (upconversion quantum yield) and performance (anti‐Stokes shift) while diminishing the cost of production. In this vein, studies employing metal‐free thermally activated delayed fluorescence (TADF) sensitizers have garnered increased interest. Here, for the first time, the strategy of ternary photon upconversion is utilized with the TADF sensitizer 2, 4, 5, 6‐tetrakis(carbazol‐9‐yl)isophthalonitrile (4CzIPN), resulting in a doubling of the upconversion quantum yield in comparison to the binary system employing p ‐terphenyl as the emitter. In this ternary blend, the sensitizer 4CzIPN is paired with an intermediate acceptor, 1‐methylnaphthalene, in addition to the emitter molecule, p ‐terphenyl, yielding a normalized upconversion quantum yield of 7.6% while maintaining the 0.83 eV anti‐Stokes shift. These results illustrate the potential benefits of utilizing this strategy of energy‐funneling, previously used only with heavy‐metal based sensitizers, to increase the performance of these photon upconversion systems. Abstract : The influence of the first three‐component metal‐free photon upconversion system on the upconversion efficiency and threshold light intensity is studied herein. While the efficiency is doubled, the threshold light intensity is also increased. The performance enhancement can be attributed to more efficient energy transfer from the sensitizer to the intermediate acceptor in combination with a high quantum yield emitter molecule.